Perbaikan Jatuh Tegangan Pada Feeder Jaringan Distribusi Tegangan Menengah 20 kV Teluk Kuantan - Hermanto Hermanto; Dian Yayan Sukma; Feranita Feranita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Electric power is the basic human needs in life. Indonesia's electricity mostly served by a stateowned company that we know the name of PT. PLN (Persero), which energy sourced electricity generated from power plants. In the town of Teluk Kuantan Kuantan Singingi source of electrical energy obtained from the substation with an installed capacity of 2 x 30 MVA, in which the high voltage transmission line 150 kV supplied from the substation Kiliranjao West Sumatra Province which consists of 6 (six) Feeder which mostly caters to needs households and industry. Along withthe development of an area, it will have an impact on the amount of electrical energy requirements will result in the distribution channel spacing between plants and consumers increasingly distant. With the longer the distribution channels and the increasing burden on the Feeder will increase power loss which resulted in a fall in voltage. To overcome these problems need to do repair them with the installation of capacitor banks and enlarging the cross sectional area Conductor mediumvoltage air channels. Before the repair needs to be calculated by using the power flow ETAP Software 7.5. After calculating for the combined method between the capacitor bank and enlargethe airway cross-sectional area Conductor medium voltage obtained the lowest percentage of voltage drop at the level of 1.52% and the highest at the level of 4.92% of the voltage sent.Keywords: Voltage drop, feeder distribution network, medium voltage 20 kV